Narcotráfico en Bolivia: resúmenes analíticos (1980 - 1993) - Carvajal A., Paola A. (Drogas - investigación para el debate, 1993)
"Excellent annotated bibliography of several dozen articles and books published between 1980-93 on narcotics trafficking and related topics. Most of the publications are Bolivian and difficult to locate; SEAMOS apparently has original copies which can be used at their library. SEAMOS is a drug education and drug abuse prevention organization which has carried out several programs in Bolivia with some US and foreign funding"--Handbook of Latin American Studies, v. 57